Contrast‐enhanced endoscopic ultrasonography can predict a higher malignant potential of gastrointestinal stromal tumors by visualizing large newly formed vessels. Issue 2 (16th July 2014) - Yamashita, Yasunobu; Kato, Jun; Ueda, Kazuki; Nakamura, Yasushi; Abe, Hiroko; Tamura, Takashi; Itonaga, Masahiro; Yoshida, Takeichi; Maeda, Hiroki; Moribata, Kosaku; Niwa, Toru; Maekita, Takao; et al.
ABSTRACT Background The aim of this study was to elucidate the histologic and clinical implications of detection of intratumoral vessels on contrast‐enhanced endoscopic ultrasonography (CE‐EUS) in gastrointestinal stromal tumors (GISTs). Methods Thirteen patients with a GIST, all of whom were referred for surgery, underwent presurgical CE‐EUS. The malignant potential, assessed according to the modified Fletcher risk classification system, and the histologic degree of angiogenesis were compared with the presence or absence of intratumoral vessels on CE‐EUS. Results Of the six tumors with intratumoral vessels observed on CE‐EUS, five were intermediate‐ or high‐risk GISTs, and the remaining seven negative cases were categorized as very low risk or low risk. The presence of intratumoral vessels on CE‐EUS was significantly correlated with a higher‐risk classification (p = 0.005). On histologic examination, all GISTs having visualized vessels incorporated vessels of more than 500 μm in diameter. The large intratumoral vessels of the five intermediate‐ or high‐risk GISTs lacked elastic fibers, suggesting that they were neovascular in nature. These higher‐risk tumors were also found, by immunohistochemical analysis, to have high expression of vascular endothelial growth factor. Conclusions Intratumoral vessels observed in GISTs on CE‐EUS are correlated with a higher degree of angiogenesis, resulting in higher malignant potential. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound, 43:89–97, 2015